Impacts of elevated terrestrial nutrient loads and temperature on pelagic food‐web efficiency and fish production. (11th February 2013) - Lefébure, R.; Degerman, R.; Andersson, A.; Larsson, S.; Eriksson, L‐O.; Båmstedt, U.; Byström, P.
Abstract: Both temperature and terrestrial organic matter have strong impacts on aquatic food‐web dynamics and production. Temperature affects vital rates of all organisms, and terrestrial organic matter can act both as an energy source for lower trophic levels, while simultaneously reducing light availability for autotrophic production. As climate change predictions for the Baltic Sea and elsewhere suggest increases in both terrestrial matter runoff and increases in temperature, we studied the effects on pelagic food‐web dynamics and food‐web efficiency in a plausible future scenario with respect to these abiotic variables in a large‐scale mesocosm experiment. Total basal (phytoplankton plus bacterial) production was slightly reduced when only increasing temperatures, but was otherwise similar across all other treatments. Separate increases in nutrient loads and temperature decreased the ratio of autotrophic:heterotrophic production, but the combined treatment of elevated temperature and terrestrial nutrient loads increased both fish production and food‐web efficiency. CDOM: Chl a ratios strongly indicated that terrestrial and not autotrophic carbon was the main energy source in these food webs and our results also showed that zooplankton biomass was positively correlated with increased bacterial production. Concomitantly, biomass of the dominant calanoid copepod Acartia sp . increased as an effect of increased temperature. As the combined effects of increased temperature and terrestrial organic nutrient loads were required to increase zooplankton abundance and fish production, conclusions about effects of climate change on food‐web dynamics and fish production must be based on realistic combinations of several abiotic factors. Moreover, our results question established notions on the net inefficiency of heterotrophic carbon transfer to the top of the food web.